A novel role of h2‐calponin in regulating whole blood thrombosis and platelet adhesion during physiologic flow. Issue 12 (3rd December 2014) - Hines, Patrick C.; Gao, Xiufeng; White, Jennell C.; D'Agostino, Ashley; Jin, Jian‐Ping
Abstract Calponin is an actin filament‐associated protein reported in platelets, although the specific isoform expressed and functional role were not identified. The h2‐calponin isoform is expressed in myeloid‐derived peripheral blood monocytes, where it regulates adhesion. Our objective was to characterize the presence and function of the h2 isoform of calponin in platelets. H2‐calponin was detected in human and mouse platelets via Western blotting. Immunofluorescent staining demonstrated h2‐calponin and actin colocalized in both human and wild‐type mouse platelets at rest and following collagen activation. The kinetics of platelet adhesion and whole blood thrombosis during physiologic flow was evaluated in a microfluidic flow‐based thrombosis assay. The time to initiation of rapid platelet/thrombus accumulation (lag time) was significantly longer in h2‐calponin knockout versus wild‐type mouse blood (130.02 ± 3.74 sec and 72.95 ± 16.23 sec, respectively, P < 0.05). There was no significant difference in the rate of platelet/thrombus accumulation during the rapid phase or the maximum platelet/thrombus accumulation. H2‐calponin knockout mice also had prolonged bleeding time and blood loss. H2‐calponin in platelets facilitates early interactions between platelets and collagen during physiologic flow, but does not significantly affect the rate or magnitude of platelet/thrombus accumulation. H2‐calponin knockout mice take 2.3 times longer to achieve hemostasis compared to wild‐type controls in a tail bleeding model. The ability to delay platelet accumulation without inhibiting downstream thrombotic potential would be of significant therapeutic value, thus h2‐calponin may be a novel target for therapeutic platelet inhibition.